[PP.19.16] SHORT-TERM RETINAL ARTERIOLAR LUMEN CHANGES ARE UNRELATED TO PERIPHERAL VASCULAR RESISTANCE CHANGES IN TREATED HYPERTENSIVE PATIENTS. (September 2017) - Gallo, A.; Girerd, X.; Laurent, S.; Levy, B.; Rosenbaum, D.
Abstract : Objective: The microcirculation is the major site of the total peripheral resistance (TPR); the arteriolar vasomotricity is its determinant. While some correlations between TPR and retinal arteriolar remodeling have been shown in a chronic setting, no prospective data exists regarding short-term changes in retinal arteriolar lumen and total resistances. Our aim was to evaluate the relations between changes in TPR and retinal microvasculature anatomical indices in uncontrolled hypertensive patients. Design and method: 29 hypertensive patients (16 males, 13 females, mean age 48 ± 14) underwent Adaptive Optics imaging using RTX1 camera® (ImagineEye, Orsay, France) to measure Wall Thickness (WT), Internal Diameter (ID), Wall Cross Sectional Area (WCSA) and Wall-to-Lumen Ratio (WLR) of retinal arterioles. The Integrated Hemodynamic System (Hotman System®) was used to calculate Stroke Systemic Vascular Resistance Index (SSVRI), an index of TPR. Among them, 10 uncontrolled hypertensive subjects (6 males, 4 females, mean age 50 ± 12) had a follow-up assessment 1 month after introduction or increase of an antihypertensive therapy. Results: At baseline, mean Systolic BP (SBP) and Diastolic BP were 147 ± 21 and 84.9 ± 13 mmHg respectively. Retinal WT, ID, WLR and WCSA were 21.8 ± 3.6 μm, 74.5 ± 12 μm, 0.299 ± 0.060 and 2954 ± 765 μm 2, respectively. Mean SSVRI was 142.4 ± 40 dyn*sec/cm 5 . In the whole population, no correlation was found between ID and SSVRI (Spearman's ρ = 0.292, p = 0.124). Baseline and follow up BP levels, retinal arteriolar anatomical indices and resistance characteristics are shown in Table 1. Figure. No caption available. At follow-up, a significant decrease in SBP was observed (−13 ± 7.5% p = 0.008) in association with a significant lumen dilatation of retinal arterioles (+11.6 ± 7.6%, p = 0.018). No significant changes were observed in other retinal parameters or in SSVRI although vasodilator drugs were used. Conclusions: Retinal arteriolar lumen dilatation was observed after short-term brachial BP reduction, and was not related to TPR decrease. This suggests that 1) the changes in retinal arteriolar network may be more easily detected than TPR changes, and/or that 2) lumen dilatation or retinal arterioles changes occur to a greater extent than at the peripheral level.